Internal funding sources of commercial banks of Kazakhstan - Zholamanova, M (Journal of Economic Research & Business Administration, 2016)
In thе article «Internal funding sources of commercial banks of Ka zakhstan» there was performed analysis of the Deposit market for the last nine years including the period of the global economic crisis (2007-2010 years) and the impact of the crisis on the pace of development of the De posit market. The pace of development and the growth rate of the Deposit market affect not only the creditworthiness of the Bank and its liquidity but macroeconomic development and the welfare of the country too.